EXPERIMENTS ON THE VOLUMETRIC MODELS OF DAMS MADE OF REIFORCED SOIL - Bekmamat, Khamdamov; Rahmanovich, Yuldashev Tashmirza; Umidjon, Khamdamov (International Journal of Psychosocial Rehabilitation, 2020)
The analysis of published works on researching, usage and exploitation of units made of reinforced soil is presented. Description of the experimental stand. Methods of getting hydrostatic pressure and intrinsic weight of the dam. Conclusions and recommendations on the results of the experimental research.